Assessing intercultural communication: Testing technology tools for information sharing in multinational research teams. (13th January 2019) - Ward, Wesley S.; Given, Lisa M.
Abstract : Agricultural research in developing countries often involves collaboration between dispersed multicultural teams of scientists from developed and developing countries. The teams use information and computing technologies (ICTs) to communicate between team members, who originate from different cultures using different languages. This paper investigates the usability and utility of a range of ICTs used for communication between team members from different cultures. The research used an intercultural heuristic evaluation tool, or I‐CHET, to evaluate nine ICTs used by Australian and Lao scientists for team communication. The evaluation showed that asynchronous ICTs (e.g., e‐mail) were preferred by non‐native English speakers, while synchronous media (e.g., audio conferencing, instant messaging, Skype) presented considerable problems between team members from different cultures. Most ICTs evaluated in the study demonstrated little consideration for non‐native English speakers and for inexperienced ICTs users. However, all evaluated ICTs demonstrated the ability to transmit information and encourage communication between information users in scientific collaborations. The I‐CHET assessment tool highlights the ongoing need for a "toolbox" of communication ICTs for research collaborations that can be adapted to suit the cultural and professional needs of multinational teams, worldwide.